Justification, development and verification of the effectiveness of the educational and training program for forming the image of officers involved in the training of cadets - Belichenko, L. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article presents the results of an experimental verification of the effectiveness of the author’s educational and training program for the formation of the image of officers involved in the training of cadets. Based on the theoretical analysis of the "image" category and the developed general system of image formation, a detailed study of the individual and psychological characteristics of the target audience (cadets) and image bearers (officers), an educational and training program was developed. It is aimed at forming a positive image of officers involved in training of cadets. The main methodical principle and mechanism of conducting any training is the opportunity to feel a lot of experiences that can be compared with experiences in real life. In particular, during the development of educational and training program, namely, the selection of training methods, following parameters were definitely taken into consideration: program tasks, program duration, group size, and what is extremely important, the level of the participants training, their previous experience, the degree of interpersonal interaction and expected activity of participants. The peculiarity of the educational and training program is not so much the passing of exercises for the development of professionally important and personal qualities of officers for the formation of a positive image, but interaction with cadets in an informal and unusual environment. Taking into consideration the specifics of the main subject of educational and training program, namely the "image" category, the proposed program can be related with both professionally oriented trainings and personal growth trainings. Therefore, the ETP provides an opportunity not only to acquire the necessary knowledge and skills for the formation of a positive image, to develop their professionally important and personal qualities, but also helps officers and cadets to show themselves from those sides that are hardly visible in everyday official activities, to look at the officer- cadet interaction on the other hand and perhaps do some re-evaluation of self and others.